Friedrich Engels and Marxian Political Economy - Hollander, Samuel (Cambridge : Cambridge University Press, 2011)
This book rejects the commonly encountered perception of Friedrich Engels as perpetuator of a 'tragic deception' of Marx, and the equally persistent body of opinion treating him as 'his master's voice'. Engels' claim to recognition is reinforced by an exceptional contribution in the 1840s to the very foundations of the Marxian enterprise, a contribution entailing not only the 'vision' but some of the building blocks in the working out of that vision. Subsequently, he proved himself to be a sophisticated interpreter of the doctrine of historical materialism and an important contributor in his own right. This volume serves as a companion to Samuel Hollander's The Economics of Karl Marx (Cambridge University Press, 2008).
Engels's Early Contribution -- The Surplus-Value Doctrine, Rodbertus's Charge of Plagiarism, and the Transformation -- Economic Organization, and the Price Mechanism -- "Revisionism" I. Constitutional Reform versus Revolution -- "Revisionism" II. Social Reform -- The Engels-Marx Relation -- A Methodological Overview -- The Immediate Legacy.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Engels, Friedrich, -- 1820-1895.; Marxian economics; Historical materialism